EQUATION OF STATE OF HEXAGONAL ALUMINOUS PHASE IN BASALTIC COMPOSITION TO 63 GPA AT 300 K - Ono S.; Hirose K.; Isshiki M.; Mibe K.; Saito Y. (My University, 2002)
A laser-heated diamond-anvil cell that is capable of operating up to a pressure of 63 GPa, with X-ray diffraction facilities using a synchrotron radiation source at the SPring-8, has been developed to observe the compressibility of a hexagonal aluminous phase, [K0.15Na1.66Ca0.11Mg1.29Fe2+0.86Al3.13Ti0.09Si1.98] Σ9.27O12. The hexagonal aluminous phase is a potassium host mineral from the subducted oceanic crust in the Earth's lower mantle. A sample was heated using a YAG laser at each pressure increment to relax the deviatoric stress in the sample. X-ray diffraction measurements were carried out at 300 K using an angle-dispersive technique. Pressure was measured using an internal platinum pressure calibrant. The observed unit-cell volumes were used to obtain a third-order Birch-Murnaghan equation of state: unit-cell volume Vo=185.94(±16) A3, density ρo=4.145 g/cm3, and bulk modulus Ko=198(±3) GPa when the first pressure is derivative of the bulk modulus K'o is fixed to 4. The density of hexagonal aluminous phase is lower than that of coexisting Mg-perovskite in the subducted oceanic crust.
Keywords: HEXAGONAL ALUMINOUS PHASE; EQUATION OF STATE; X-RAY POWDER DIFFRACTION